Frankenstein’s Singular Events: Inductive Reasoning, Narrative Technique, and Generic Classification - Morgan, Monique (Romanticism on the Net, 2006)
AbstractIn this essay, I suggest that the central section of Mary Shelley’s Frankenstein – the creature’s description of his first experiences – echoes Hume’s and Bacon’s discussions of inductive reasoning. Because the creature must learn the causes of phenomena the reader takes for granted, his story defamiliarizes both the reader’s world and the process of induction itself. The creature’s tale thus functions as a travel narrative, and produces the cognitive estrangement associated with science fiction. I then examine the prominence of inductive reasoning in the novel as a whole, and discuss Victor’s and the creature’s singular situations as resistant to inductive understanding. I argue that Shelley uses various narrative techniques (such as embedded narratives and character doubling) to invite and frustrate readers’ attempts to use induction to solve the novel’s central moral questions. The reader’s inability to form coherent inductive patterns in part accounts for the novel’s radical ambiguity. Finally, I suggest some consequences for Frankenstein’s relation to the gothic: the novel departs from gothic conventions in its unusual use of the doppelgänger, and its rhetorical goals in invoking induction.